Animal Naming Test Is Associated With Poor Patient-Reported Outcomes and Frailty in People With and Without Cirrhosis: A Prospective Cohort Study. Issue 1 (12th January 2022) - Tapper, Elliot B.; Kenney, Brooke; Nikirk, Samantha; Levine, Deborah A.; Waljee, Akbar K.
Abstract : INTRODUCTION: Cognitive dysfunction is a major driver of care complexity, poor patient-reported outcomes, and frailty for people with cirrhosis. The performance and clinical associations of the animal naming test (ANT) in the general population are unknown. We evaluated ANT performance in a representative sample of older Americans with and without chronic liver disease (CLD). METHODS: We analyzed 6, 661 subjects enrolled in the 2010–2016 Health and Retirement Survey, a representative cohort of >30, 000 US adults. Average age of participants was 75 years. We evaluated 3 subject subgroups: (i) without CLD, (ii) noncirrhosis CLD, and (iii) cirrhosis. We determined the association between the ANT (overall) and S-ANT1 <10 (adjusted for age and education) and health status, basic and instrumental activities of daily living, healthcare utilization (care hours received and hospitalizations), and frailty measures (hand grip and walk speed). RESULTS: Overall, 8.2% of the sample had noncirrhotic CLD and 1.3% had cirrhosis. CLD or cirrhosis was not independently associated with ANT. Poor ANT performance was associated with poor health status and frailty overall. An S-ANT <10 was associated with fair-poor self-reported health (odds ratio [OR] 1.37; 95% confidence interval [CI]: 1.20–1.56), care hours received (incidence rate ratio [IRR] 2.39; 95% CI: 1.79–3.19), and hospitalizations (IRR 1.14; 95% CI: 1.03–1.26). S-ANT <10 was also associated with activities of daily living disability (OR 1.31; 95% CI: 1.13–1.51), instrumental activities of daily living disability (OR 1.85; 95% CI: 1.59–2.14), weaker hand grip (IRR 0.94; 95% CI: 0.92–0.96), and time to walk 2.5 m (IRR 1.23; 95% CI: 1.17–1.29). DISCUSSION: ANT performance is not specific to CLD/cirrhosis but is associated with patient-reported outcomes and frailty in a nationally representative sample of elderly subjects with and without CLD.